Total Plate Count (TPC) and Organoleptic Test on Beef Meatballs with Moringa (Moringa oleifera) Leaf Flour Addition - Hakim, Khaerul; Suharyanto, Suharyanto; Haryanto, Haryanto; Ali, M.; Sulistyowati, Endang; Bilyaro, Woki; Soetrisno, Edi (AGRITROPICA : Journal of Agricultural Sciences, 2025)
Meat refers to parts of an animal's body, such as liver, kidneys, brain, and other muscle tissues that are edible, and meat has a fairly complete nutritional content. Meatballs are a type of food popular in Indonesia, but are prone to spoilage due to the activity of microorganisms. The production of beef meatballs with the addition of moringa leaf powder (Moringa oleifera) can inhibit microbial growth and affect the quality of beef meatballs. This study aims to evaluate the effect of Moringa oleifera (Moringa leaf flour, MLF) addition on total microbes and organoleptic of beef meatballs, including color, texture, taste, and preference for color, aroma/smell, texture, and flavor. The research method used a completely randomized design (CRD) with four treatments: meatballs without the addition of MLF (T0) and meatballs with the addition of MLF 1% (T1), 2% (T2), and 3% (T3). The parameters observed included measurements, total microbes, and organoleptic characteristics, which included hedonic and sensory quality tests of beef meatballs. The results showed that the addition of moringa flour had a significant effect (P<0.05) on the results of hedonic and organoleptic quality tests but had no significant effect (P>0.05) on total microbes. The study results show that adding MLF at different levels does not effectively suppress the microbial growth of beef meatballs. Adding MLF with different levels in beef meatballs does not effectively suppress microbial growth. The addition of MLF in the hedonic and organoleptic quality tests significantly affected color, texture, smell, and taste, and was still acceptable to the panelists.